A Case Study: The Case of PPB Hartabina Sdn. Bhd. - Choong, Chee Yoong (1997)
PPB Hartabina Sdn Bhd is a 100% subsidiary of Perlis Plantations Bhd. The latter is one of the listed companies on the Kuala Lumpur Stock Exchange under the stable of companies controlled by Kuok Bros. Sdn Bhd. The case on PPB Hartabina Sdn Bhd is written with the intention to explore and review into new direction(s) the company can undertake for its future expansion and growth. It looks into the company's history, set-up, place and relationship in general with the group of companies under the conglomerate of Perlis Plantations Bhd. It is also written with the purpose of viewing the company from a distant and unattached, hopefully fresh and revealing perspective as to the potential the company has. In conclusion, the strategy for PPB Hartabina Sdn Bhd is as follows: Priority 1 : To concentrate on its own property development especially the Phase 2 Residential Development Taman Segar,Cheras, Kuala Lumpur to generate the cash flow and profits for future investments in land banks.Priority 2 : To develop the property management arm to ensure the various commercial buildings and shopping complexes own by itself or the Pedis Plantations Group of companies, are being maintained in high standard and, thus conserving and enhancing their capital values. Priority 3: On a lower priority, to provide project management services for the rest of the associated and sister companies of the Group, as and when the need arises, though there may be surplus staffing resources which may be not efficiently utilized during the intermittent period.